Household Food Insecurity in Southeastern Iran: Severity and Related Factors - Zinat Mortazavi; Ahmad Reza Dorosty; Mohammad Reza Eshraghian; Mohtasham Ghaffari; Alireza Ansari-Moghaddam; Mahdi Mohammadi (International Journal of Food Science)
Background. Today, more than one billion people globally suffer from poverty and food insecurity. This study aimed to determine the severity of and factors related to household food insecurity in Zahedan, Southeastern Iran. Methods. This cross-sectional study was conducted on a total of 2,160 households between November 2014 and December 2015. Demographic and socioeconomic data were collected through interviewing the household mothers. Household food security status was assessed through the USDA 18-item questionnaire. The data were analyzed using chi-square test, one-way ANOVA, and logistic regression model. Results. Total food insecurity in the households investigated was 58.8%. There were significant associations (P<0.001) between household food insecurity status and the socioeconomic status of the households, ethnicity, education, age, and employment status of the head of the household and the mother of the household. Discussion. The results showed that more than half of the households examined suffer from food insecurity. Interventions to improve the food security status of people should be designed and implemented to improve people’s knowledge, skills, and attitudes related to healthy eating and food preparation. People’s access to healthy foods and knowledge of how to select healthy foods (especially on a limited budget) should also be improved.